1980
DOI: 10.1017/s0022215100090253
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cryosurgery and submucous diathermy in vasomotor rhinitis

Abstract: Cryosurgery in obstructive non-allergic vasomotor rhinitis is a simple outpatient procedure with as good results as the more time-consuming and elaborate procedure of submucosal diathermy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 3 publications
2
33
1
Order By: Relevance
“…Elwany and Harrison (1990) showed a high success rate (75 per cent) after PIT compared to a 45 per cent success rate after CS. In contrast to Elwany and Harrison (1990) and our study, others have found a high success rate in CS, Bumsted (1984) 92 per cent, Chiossone et al (1990) 83 per cent, Principato (1979) 80 per cent, and Moore and Bicknell (1980) 78 per cent success rate in CS.…”
Section: The Rate Of Success Of the Procedurescontrasting
confidence: 99%
See 1 more Smart Citation
“…Elwany and Harrison (1990) showed a high success rate (75 per cent) after PIT compared to a 45 per cent success rate after CS. In contrast to Elwany and Harrison (1990) and our study, others have found a high success rate in CS, Bumsted (1984) 92 per cent, Chiossone et al (1990) 83 per cent, Principato (1979) 80 per cent, and Moore and Bicknell (1980) 78 per cent success rate in CS.…”
Section: The Rate Of Success Of the Procedurescontrasting
confidence: 99%
“…Other studies confirmed our finding and supported our approach that CS can be performed as an outpatient procedure: (Moore and Bicknell, 1980;Bumsted, 1984;Elwany and Harrison, 1990). In PIT, the main complication reported by others was bleeding in nine per cent (Dawes, 1987), or five per cent of the cases (Elwany and Harrison, 1990).…”
Section: Morbiditysupporting
confidence: 90%
“…[1][2][3][4][5][6][7] Submucosal and intramural techniques are known for their relative lack of complications, which are often mild and typically include bleeding and crusting. ITH is commonly associated with chronic allergic or vasomotor rhinitis, which affects an estimated 30 million Americans.…”
Section: Introductionmentioning
confidence: 99%
“…1 Treatment of CR consists of irritant avoidance, pharmacotherapy, and surgical treatment such as radiofrequency inferior turbinate reduction (RFITR). 2 …”
mentioning
confidence: 99%